Adhesive
The adhesive with bisphenol F-type resin and controlled magnetic powder content addresses high viscosity issues, ensuring magnetic permeability and ease of handling in coil component manufacturing.
Patent Information
- Application Number
- JP2023123050
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-28
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2043-07-28
AI Technical Summary
The adhesive used in coil components containing magnetic powder has high viscosity, making it difficult to handle during application, while ensuring sufficient magnetic permeability.
An adhesive comprising bisphenol F-type resin, a hardener, and magnetic powder with a number average molecular weight of 312 g/mol to 360 g/mol and a volume ratio of magnetic powder of 35 vol% or less, along with a silane coupling agent and dispersant, to maintain magnetic permeability and improve handling.
The adhesive ensures sufficient magnetic permeability while facilitating easy handling during manufacturing, particularly in continuous printing applications.
Smart Images

Figure 2025019436000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to adhesives. [Background technology]
[0002] The coil component described in Patent Document 1 includes a core. The core has a winding core portion and two flange portions. The winding core portion is in the shape of a rectangular prism. The two flange portions are connected to both sides of the winding core portion. Each flange portion protrudes outward from the winding core portion in a direction perpendicular to the central axis of the winding core portion. The core is made of a magnetic material. The coil component also includes a top plate. The top plate is in the shape of a substantially rectangular plate. The top plate is connected to the core so as to bridge the two flange portions. The coil component includes an adhesive. The adhesive is interposed between the top plate and the core. The adhesive bonds the top plate and the core to each other. The adhesive also includes magnetic powder. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2021-190633 A Summary of the Invention [Problem to be solved by the invention]
[0004] The adhesive applied to the coil component described in Patent Document 1 contains magnetic powder, and thus has a higher magnetic permeability than an adhesive that does not contain magnetic powder. On the other hand, the greater the content of magnetic powder in the adhesive, the higher the viscosity of the adhesive tends to be. If the viscosity of the adhesive is excessively high, for example, when applying the adhesive to a top plate using a jig, a phenomenon such as the adhesive pulling strings between the jig and the top plate occurs. In other words, the adhesive becomes difficult to handle when applied due to the increased viscosity of the adhesive. Therefore, there is a demand for an adhesive that is easy to handle during manufacturing while ensuring sufficient magnetic permeability. [Means for solving the problem]
[0005] In order to solve the above problems, the present invention provides an adhesive containing a bisphenol F type resin, a curing agent for the bisphenol F type resin, and a magnetic powder, wherein the volume ratio of the magnetic powder to the adhesive is 35 vol% or less, and the number average molecular weight of the bisphenol F type resin is 312 g / mol or more and 360 g / mol or less. Effect of the Invention
[0006] According to the above-mentioned configuration, the adhesive can be easily handled during production while ensuring a sufficient magnetic permeability. [Brief description of the drawings]
[0007] [Figure 1] FIG. 1 is a perspective view of a coil component. [Diagram 2] FIG. 2 is an exploded perspective view of the coil component. [Diagram 3] FIG. 3 is a schematic diagram of the adhesive before hardening. [Figure 4] FIG. 4 is a graph showing the test results of the yarn breaking time. [Diagram 5] FIG. 5 is a graph showing the test results of the yarn breaking time. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] Hereinafter, an embodiment of a coil component including an adhesive will be described with reference to the drawings. Note that the drawings may show components enlarged for ease of understanding. The dimensional ratios of the components may differ from those in the actual product or from those in other drawings.
[0009] <About coil components> As shown in FIG. 1, the coil device 10 includes a drum core 10C as a first core, and a top plate 10F as a second core.
[0010] The drum core 10C has a winding core 11. The winding core 11 is a square prism having a central axis 11C. A cross section of the winding core 11 perpendicular to the central axis 11C is rectangular. The "rectangular shape" referred to here may be any shape having four sides and generally rectangular, and may also include a shape with chamfered corners. The material of the winding core 11 is, for example, alumina, Ni-Zn ferrite, synthetic resin, or a mixture thereof. In this embodiment, the material of the winding core 11 is Ni-Zn ferrite, which is a type of magnetic material.
[0011] Here, a specific axis perpendicular to the central axis 11C of the winding core 11 is defined as the first axis X. In this embodiment, the first axis X is parallel to the two short sides of the winding core 11 when viewed in the direction along the central axis 11C. An axis perpendicular to both the first axis X and the central axis 11C is defined as the second axis Y. In this embodiment, the second axis Y is parallel to the two long sides of the winding core 11 when viewed in the direction along the central axis 11C. An axis parallel to the central axis 11C is defined as the third axis Z. One of the directions along the first axis X is defined as the first positive direction X1, and the opposite direction to the first positive direction X1 is defined as the first negative direction X2. Similarly, one of the directions along the second axis Y is defined as the second positive direction Y1, and the opposite direction to the second positive direction Y1 is defined as the second negative direction Y2. Moreover, one of the directions along the third axis Z is defined as a third positive direction Z1, and the direction opposite to the third positive direction Z1 is defined as a third negative direction Z2.
[0012] As shown in FIG. 1, the drum core 10C has two flanges 20 connected to both ends of the winding core 11 in the direction along the central axis 11C. The two flanges 20 are specifically a first flange 21 and a second flange 22. The first flange 21 is connected to a first end of the winding core 11 in the third positive direction Z1. The first flange 21 has a flat, substantially rectangular plate shape. The thickness direction of the first flange 21 is a direction along the third axis Z. When viewed in the direction along the third axis Z, each side of the first flange 21 is substantially parallel to each side of the winding core 11. The first flange 21 protrudes outward from the outer surface of the winding core 11 in the direction along the first axis X and the direction along the second axis Y. That is, when viewed in a direction along the third axis Z, the first flange portion 21 protrudes from the outer surface of the winding core portion 11 over the entire circumference of 360 degrees.
[0013] The first flange 21 has a first recess 21A. The first recess 21A is recessed with respect to an end face of the first flange 21 in the first positive direction X1. The first recess 21A is located at the center of the first flange 21 in the direction along the second axis Y. The first recess 21A is open to both sides of the first flange 21 in the direction along the third axis Z. As a result, the end face of the first flange 21 on the first positive direction X1 side is divided into two parts with the first recess 21A in between.
[0014] The second flange 22 is connected to a second end of the winding core 11 on the third negative direction Z2 side. The second flange 22 has a shape that is plane-symmetrical to the first flange 21. That is, the second flange 22 is a substantially rectangular plate shape. The second flange 22 protrudes outward from the outer surface of the winding core 11 in the direction along the first axis X and the direction along the second axis Y. That is, the second flange 22 protrudes 360 degrees from the outer surface of the winding core 11 when viewed in the direction along the third axis Z. The second flange 22 has a second recess 22A similar to the first recess 21A of the first flange 21. The material of the first flange 21 and the second flange 22 is the same Ni-Zn ferrite as the winding core 11. That is, the drum core 10C is made of a magnetic material. The first flange 21 and the second flange 22 are integrally formed with the winding core 11.
[0015] The top plate 10F is a flat rectangular plate. The thickness direction of the top plate 10F is along the first axis X. The long side of the top plate 10F is parallel to the third axis Z. The short side of the top plate 10F is parallel to the second axis Y. The top plate 10F is located on the first negative direction X2 side with respect to the drum core 10C. The top plate 10F is connected to both the surface of the first flange portion 21 facing the first negative direction X2 side and the surface of the second flange portion 22 facing the first negative direction X2 side. In other words, the top plate 10F is connected to the drum core 10C so as to bridge between the first flange portion 21 and the second flange portion 22. The material of the top plate 10F is the same as that of the winding core portion 11. In other words, the top plate 10F is Ni-Zn ferrite, which is a type of magnetic material. The top plate 10F forms a closed magnetic circuit together with the drum core 10C. In this embodiment, the top plate 10F, on which the wires described later are not directly wound, and the flange portion 20 of the drum core 10C, on which the wires are not wound, are also considered to be the core or a part of the core.
[0016] The coil component 10 includes an adhesive 50. The adhesive 50 is interposed between the drum core 10C and the top plate 10F. That is, the adhesive 50 bonds the drum core 10C and the top plate 10F. In this embodiment, the drum core 10C and the top plate 10F are in direct contact with the adhesive 50. In other words, the top plate 10F is connected to the two flanges 20 via the adhesive 50. Details of the adhesive 50 will be described later.
[0017] The coil component 10 includes four external electrodes 30. Specifically, the coil component 10 includes a first electrode 31, a second electrode 32, a third electrode 33, and a fourth electrode 34. The first electrode 31 is located on an end face of the outer surface of the first flange portion 21 on the first positive direction X1 side. The first electrode 31 is located on the outer surface of the first flange portion 21 on the second positive direction Y1 side with respect to the central axis 11C. Specifically, the first electrode 31 is located on the second positive direction Y1 side with respect to the first recess 21A.
[0018] The second electrode 32 is located on the end face on the first positive direction X1 side of the outer surface of the first flange 21. The second electrode 32 is located on the second negative direction Y2 side with respect to the central axis 11C of the outer surface of the first flange 21. Specifically, the second electrode 32 is located on the second negative direction Y2 side with respect to the first recess 21A.
[0019] The third electrode 33 is located on the end face on the first positive direction X1 side of the outer surface of the second flange 22. The third electrode 33 is located on the second positive direction Y1 side with respect to the central axis 11C of the outer surface of the second flange 22. Specifically, the third electrode 33 is located on the second positive direction Y1 side with respect to the second recess 22A.
[0020] The fourth electrode 34 is located on the end face on the first positive direction X1 side of the outer surface of the second flange 22. The fourth electrode 34 is also located on the second negative direction Y2 side with respect to the central axis 11C of the outer surface of the second flange 22. Specifically, the fourth electrode 34 is located on the second negative direction Y2 side with respect to the second recess 22A.
[0021] Although not shown in the figure, the external electrode 30 has a metal layer and a plating layer. The material of the metal layer is silver. The metal layer is formed on the outer surfaces of the first flange portion 21 and the second flange portion 22. The plating layer is made of three layers. The plating layer is formed by stacking copper, nickel, and tin in this order on the surface of the metal layer. The end face of the coil component 10 on the first positive direction X1 side is a mounting surface that faces the board when the coil component 10 is mounted on the board.
[0022] 1, the coil device 10 includes a first wire 41 and a second wire 42. The first wire 41 and the second wire 42 are wound around the winding core portion 11 of a drum core 10C.
[0023] Although not shown, the first wire 41 has a copper wire and an insulating coating. The insulating coating covers the outer surface of the copper wire. The first wire 41 has a substantially circular shape in a cross section perpendicular to the direction in which the first wire 41 extends. The second wire 42 has the same configuration as the first wire 41. That is, the second wire 42 has a copper wire and an insulating coating. Note that in FIG. 1, the first wire 41 is colored with dots.
[0024] A first wire end 41A of the first wire 41 is connected to the first electrode 31. A second wire end 41B of the first wire 41 is connected to the third electrode 33. The first wire end 41A and the second wire end 41B are connected to the corresponding external electrodes 30 by thermocompression bonding.
[0025] In addition, the first wire 41 is wound around the winding core 11 so as to progress clockwise from the first wire end 41A side to the second wire end 41B side when viewed in the third negative direction Z2.
[0026] A first end 42A of the second wire 42 is connected to the second electrode 32. A second end 42B of the second wire 42 is connected to the fourth electrode 34. The first end 42A and the second end 42B are connected to the corresponding electrodes by thermocompression.
[0027] Furthermore, the second wire 42 is wound around the winding core 11 so as to progress clockwise as it travels from the first wire end 42A to the second wire end 42B when viewed in the third negative direction Z2. That is, the second wire 42 is wound in the same direction as the first wire 41. The second wire 42 is wound around the winding core 11 from the outside relative to the first wire 41.
[0028] <About adhesives> As shown in FIG. 2, the adhesive 50 covers the entire surface of the first flange 21 facing the first negative direction X2. The adhesive 50 connects the first flange 21 and the top plate 10F without any gaps. Similarly, the adhesive 50 covers the entire surface of the second flange 22 facing the first negative direction X2. The adhesive 50 connects the second flange 22 and the top plate 10F without any gaps. In other words, the top plate 10F is connected to the two flanges 20.
[0029] As shown in Fig. 3, the adhesive 50 contains bisphenol F type resin 51, magnetic powder 52, a curing agent 53, a curing accelerator 54, a silane coupling agent 55, and a dispersant 56. Note that the adhesive 50 shown in Fig. 3 is in a state before curing. Also, in Fig. 3, only some of the magnetic powder 52, the curing agent 53, and the curing accelerator 54 are labeled with reference numerals.
[0030] Specifically, the adhesive 50 is manufactured as follows. First, the bisphenol F type resin 51, the curing agent 53, the curing accelerator 54, the silane coupling agent 55, the dispersant 56, and the magnetic powder 52 are mixed for 5 minutes at a rotation speed of 30 rpm using a kneader (model number: Hibismix (registered trademark) 2P-03 (manufactured by Primix Corporation)). Then, the mixture is kneaded at a clearance of 6 μm and 230 rpm using a disperser (model number: EXAKT 80E (manufactured by Nagase Screen Printing Laboratory Co., Ltd.)) to manufacture the adhesive 50 before curing.
[0031] In this embodiment, the bisphenol F type resin 51 is a bisphenol F type epoxy resin. Specifically, the bisphenol F type resin 51 is CAS No. 9003-36-5. In this embodiment, the bisphenol F type resin 51 is collectively referred to as the bisphenol F type resin 51 regardless of whether it is a monomer or a polymer.
[0032] The number average molecular weight of the bisphenol F type resin 51 is 312 g / mol. The number average molecular weight of the bisphenol F type resin 51 may be 312 g / mol or more and 360 g / mol or less. The number average molecular weight can be measured using a GPC (model number: HLC-8120GPC (manufactured by Tosoh Technosystems)). GPC stands for gel permeation chromatography. In the measurement using this device, the column temperature was 40°C. In addition, tetrahydrofuran was used as the solvent in the measurement. The flow rate of the solution containing the solvent was 1.0 ml / min. In addition, the standard sample was monodisperse polystyrene.
[0033] In this embodiment, the volume ratio of the bisphenol F resin 51 to the adhesive 50 is 54.5 vol%. A more preferable volume ratio of the bisphenol F resin 51 to the adhesive 50 is 54.4 vol% or more and 68.7 vol% or less. The "volume ratio to the adhesive 50" is the ratio of the volume to the entire volume of the adhesive 50 before hardening, expressed as a percentage.
[0034] In this embodiment, the magnetic powder 52 is nickel powder. Specifically, the magnetic powder 52 is CAS No. 7440-02-0. The magnetic powder 52 contains particles having a particle size of 0.1 μm or more and 3.0 μm or less. The volume ratio of the magnetic powder 52 to the adhesive 50 is 35 vol% or less. In this embodiment, the volume ratio of the magnetic powder 52 to the adhesive 50 is 35 vol%. The volume ratio of the magnetic powder 52 to the adhesive 50 may be 35 vol% or less, and is preferably 20 vol% or more.
[0035] In the particle size distribution of the magnetic powder 52, the median particle size (D50) is 0.8 μm or more and 2.5 μm or less. The median particle size (D50) of the magnetic powder 52 is calculated, for example, as follows. First, the magnetic powder 52 is sampled using a scanning electron microscope to obtain the particle size distribution. Next, in the particle size distribution, the frequency of each particle size is integrated from the smallest particle size to the largest particle size. The particle size at which the integrated value is 50% is defined as the median particle size (D50).
[0036] The curing agent 53 is a curing agent for the bisphenol F type resin 51. In this embodiment, the curing agent 53 is dicyandiamide. Specifically, the curing agent 53 is CAS No. 461-58-5. The volume ratio of the curing agent 53 to the adhesive 50 is 4.36 vol%. It is more preferable that the volume ratio of the curing agent 53 to the adhesive 50 is 4.36 vol% or more and 5.49 vol% or less.
[0037] The curing accelerator 54 is a curing accelerator for the bisphenol F type resin 51. In this embodiment, the curing accelerator 54 is an amine adduct. Specifically, the curing accelerator 54 is CAS No. 134091-75-1. The volume ratio of the curing accelerator 54 to the adhesive 50 is 2.73 vol%. It is more preferable that the volume ratio of the curing accelerator 54 to the adhesive 50 is 2.72 vol% or more and 3.43 vol% or less.
[0038] The dispersant 56 is for dispersing the magnetic powder 52 in the adhesive 50. In this embodiment, the dispersant 56 is a modified carboxyl group-containing polymer. Specifically, the dispersant 56 is a modified carboxyl group-containing polymer with an acid value of 55 mgKOH / g. The volume ratio of the dispersant 56 to the adhesive 50 is 3.1 vol%. It is more preferable that the volume ratio of the dispersant 56 to the adhesive 50 is 2.18 vol% or more and 3.13 vol% or less.
[0039] In this embodiment, the silane coupling agent 55 is glycidoxypropyltrimethoxysilane. Specifically, the silane coupling agent 55 is CAS No. 253-83-8. The volume ratio of the silane coupling agent 55 to the adhesive 50 is 0.3 vol%. More preferably, the volume ratio of the silane coupling agent 55 to the adhesive 50 is 0.24 vol% or more and 0.35 vol% or less.
[0040] <Characteristics of adhesive> The glass transition temperature of the adhesive 50 after curing is 125°C or higher. The glass transition temperature of the adhesive 50 was measured as follows. First, bisphenol F type resin 51, curing agent 53, curing accelerator 54, silane coupling agent 55, dispersant 56, and magnetic powder 52 were mixed, and then baked in an atmosphere of 150°C for 3 hours to prepare a cured adhesive test piece. The dimensions of the adhesive test piece were 20 mm in length, 10 mm in width, and 1.5 mm in thickness. Then, both short sides of the above adhesive test piece were fixed to a viscoelasticity measuring device (model number: DMS7100 (manufactured by Hitachi High-Technologies Corporation)), and the elastic modulus was measured. In the measurement, the test atmosphere was heated while a sine wave force with a frequency of 1 Hz was applied to the adhesive test piece. The heating rate was 5°C / min, and the temperature range was set to 25°C to 280°C. The change in the elastic modulus of the adhesive test piece with respect to the temperature increase was measured, and the inflection point was determined as the glass transition temperature.
[0041] The adhesive strength of the adhesive 50 after curing is 10 MPa or more. The adhesive strength of the adhesive 50 was measured as follows. First, the bisphenol F type resin 51, the curing agent 53, the curing accelerator 54, the dispersant 56, the silane coupling agent 55, and the magnetic powder 52 were mixed to obtain the adhesive 50 before curing. Then, the adhesive 50 was applied between two alumina substrates in a 5 mm square area. Therefore, in this measurement, the adhesive strength per 25 square millimeters can be measured. Then, the two alumina substrates to which the adhesive 50 before curing was applied were baked in an atmosphere of 150°C for 3 hours to prepare a cured adhesive test piece. Then, one alumina substrate and the other alumina substrate were fixed to an autograph (model number: AG XD Plus (manufactured by Shimadzu Corporation)), and a tensile test was performed. That is, in this embodiment, the tensile adhesive strength was measured as the adhesive strength. In the test, the tensile speed was 20 mm / min. The load at which the adhesion test piece broke was determined as the adhesive strength of the adhesive 50. The test environment was at a temperature of 23° C. and a relative humidity of 50%.
[0042] <Continuous printing of adhesive> Four samples of the adhesive 50 with different number average molecular weights of the bisphenol F type resin 51 were prepared, and the thread breakage time of each sample was measured. The conditions of the four samples were the same except for the number average molecular weight of the bisphenol F type resin 51. The volume ratio of the magnetic powder 52 in each of the four samples was 35 vol%. The volume ratio here is the volume ratio in the adhesive 50 before hardening. The thread breakage time is the time from when the adhesive 50 before hardening is applied to a substrate with a squeegee using a screen printing machine and then the squeegee is removed from the substrate until the adhesive 50 stretched between the squeegee and the substrate is broken. In the measurement of the thread breakage time, the conditions of the screen printing machine were a printing speed of 60 mm / s, a printing pressure of 0.2 MPa, a back pressure of 0.125 MPa, and a clearance of 1 mm. Under these conditions, the thread breakage times were measured for the first, 25th, 50th, and 100th printings when printing was performed continuously 100 times, and the average value was taken as the representative value of the thread breakage time.
[0043] The number average molecular weight of the bisphenol F resin 51 in the first sample was 312 g / mol, the same as in the above embodiment. The number average molecular weight of the bisphenol F resin 51 in the second sample was 340 g / mol. The number average molecular weight of the bisphenol F resin 51 in the third sample was 360 g / mol. The number average molecular weight of the bisphenol F resin 51 in the fourth sample was 380 g / mol. These four types of samples are Examples 1, 2, and 3 and Comparative Example 1 described in Table 1 below.
[0044] As shown in FIG. 4, the thread cutting time in the first sample was 11 seconds. The thread cutting time in the second sample was 12 seconds. The thread cutting time in the third sample was 20 seconds. The thread cutting time in the fourth sample was 80 seconds. Thus, it was found that the thread cutting time becomes longer as the number average molecular weight of the bisphenol F type resin 51 in the adhesive 50 becomes larger. In addition, it was found that the thread cutting time becomes longer rapidly when the number average molecular weight of the bisphenol F type resin 51 exceeds 360 g / mol. In other words, it was found that the inflection point of the thread cutting time with respect to the increase in the number average molecular weight is about 360 g / mol. In addition, when applying the adhesive 50 using a screen printing machine, the longer the thread cutting time, the longer the waiting time with the squeegee separated from the substrate, and the worse the continuous printability. From this, from the viewpoint of handling the adhesive 50, it can be said that the number average molecular weight of the bisphenol F type resin 51 in the adhesive 50 is preferably 360 g / mol or less.
[0045] In addition, five samples of the adhesive 50 with different volume ratios of the magnetic powder 52 were prepared, and the thread breakage time of each sample was measured. The conditions other than the volume ratio of the magnetic powder 52 were the same for the five samples. The number average molecular weight of the bisphenol F type resin 51 in the five samples was 340 g / mol. The definition of the thread breakage time was the same as that described above. The volume ratio of the magnetic powder 52 in the first sample was 20 vol%. The volume ratio of the magnetic powder 52 in the second sample was 25 vol%. The volume ratio of the magnetic powder 52 in the third sample was 30 vol%. The volume ratio of the magnetic powder 52 in the fourth sample was 35 vol%. The volume ratio of the magnetic powder 52 in the fifth sample was 40 vol%. The volume ratio here is the volume ratio in the adhesive 50 before hardening. These five samples are Example 4, 5, 6, 2, and Comparative Example 2 described in Table 1 below.
[0046] As shown in FIG. 5, the thread cutting time in the first sample was 10 seconds. The thread cutting time in the second sample was 10 seconds. The thread cutting time in the third sample was 11 seconds. The thread cutting time in the fourth sample was 12 seconds. The thread cutting time in the fifth sample was 80 seconds. That is, it was found that when the volume ratio of the magnetic powder 52 in the adhesive 50 exceeds 35 vol%, the thread cutting time becomes suddenly longer. That is, it was found that the inflection point of the thread cutting time with respect to the increase in the volume ratio of the magnetic powder 52 is about 35 vol%. From this, it can be said that from the viewpoint of handling the adhesive 50, it is preferable that the volume ratio of the magnetic powder 52 in the adhesive 50 is 35 vol% or less.
[0047] <About the comparative test> The adhesives of Examples 1 to 9 and Comparative Examples 1 and 2 shown in Tables 1 and 2 below were prepared. The adhesives of these Examples and Comparative Examples were tested for their properties before and after curing. In the adhesives of Examples 1 to 9 and Comparative Examples 1 and 2, the synthetic resin is a bisphenol F type epoxy resin. In the adhesives of Examples 1 to 6 and Comparative Examples 1 and 2, the median particle size (D50) of the magnetic powder 52 is 0.8 μm. In addition, the adhesives of Examples 1 to 9 and Comparative Examples 1 and 2 each contain the magnetic powder 52, the curing agent 53, the curing accelerator 54, the silane coupling agent 55, and the dispersant 56.
[0048] <Regarding Examples 1 to 6> The results of the comparative test of the adhesives of Examples 1 to 6, Comparative Example 1 and Comparative Example 2 will be described below.
[0049] [Table 1]
[0050] As shown in Table 1, in the adhesive of Example 1, the number average molecular weight of the bisphenol F type resin 51 is 312 g / mol. In the adhesive of Example 1, the volume ratio of the magnetic powder 52 is 35 vol%. In the adhesive of Example 1, in a state before curing, the viscosity is 1833 Pa·s. In the adhesive of Example 1, in a state after curing, the magnetic permeability is 2.5. In the adhesive of Example 1, in a state after curing, the glass transition temperature is 125° C. In the adhesive of Example 1, in a state after curing, the adhesive strength is 14 MPa.
[0051] The viscosity was measured using a rotational rheometer (model number: MCR302 (manufactured by Anton Paar)). In the measurement using this device, a cone plate with a diameter of 25 mm was used. In the measurement, the rotation mode was set to flow curve, and the shear rate was set to 0.01 s -1 The temperature of the test environment was 25°C.
[0052] The magnetic permeability was measured as follows. First, a bisphenol F type resin 51, a curing agent 53, a curing accelerator 54, a dispersant 56, a silane coupling agent 55, and a magnetic powder 52 were mixed to obtain an adhesive 50 before curing. The adhesive 50 was then baked for 1 hour in an atmosphere at 85°C to obtain a semi-cured adhesive 50. The semi-cured adhesive 50 was then filled into a mold having an outer diameter of Φ16 mm and an inner diameter of Φ10 mm, and a toroidal core was obtained by heating and pressing the toroidal core for 15 minutes under pressure conditions of 4 MPa and a heating temperature of 150°C using a small heat press machine (model number: H300-15 (manufactured by AS ONE)). The toroidal core was measured using an impedance analyzer (model number: E4991A (manufactured by Keysight Technologies)) under conditions of 10 MHz, and the measured real magnetic permeability was taken as the magnetic permeability. The temperature of the test environment was 25°C.
[0053] In the adhesive of Example 2, the number average molecular weight of the bisphenol F type resin 51 is 340 g / mol. In the adhesive of Example 2, the volume ratio of the magnetic powder 52 is 35 vol%. In the adhesive of Example 2, before curing, the viscosity is 2528 Pa·s. In the adhesive of Example 2, after curing, the magnetic permeability is 2.5. In the adhesive of Example 2, after curing, the glass transition temperature is 125° C. In the adhesive of Example 2, after curing, the adhesive strength is 14 MPa.
[0054] In the adhesive of Example 3, the number average molecular weight of the bisphenol F type resin 51 is 360 g / mol. In the adhesive of Example 3, the volume ratio of the magnetic powder 52 is 35 vol%. In the adhesive of Example 3, before curing, the viscosity is 3223 Pa·s. In the adhesive of Example 3, after curing, the magnetic permeability is 2.5. In the adhesive of Example 3, after curing, the glass transition temperature is 125° C. In the adhesive of Example 3, after curing, the adhesive strength is 14 MPa.
[0055] In the adhesive of Example 4, the number average molecular weight of the bisphenol F type resin 51 is 340 g / mol. In the adhesive of Example 4, the volume ratio of the magnetic powder 52 is 20 vol%. In the adhesive of Example 4, before curing, the viscosity is 283 Pa·s. In the adhesive of Example 4, after curing, the magnetic permeability is 1.7. In the adhesive of Example 4, after curing, the glass transition temperature is 125° C. In the adhesive of Example 4, after curing, the adhesive strength is 14 MPa.
[0056] In the adhesive of Example 5, the number average molecular weight of the bisphenol F type resin 51 is 340 g / mol. In the adhesive of Example 5, the volume ratio of the magnetic powder 52 is 25 vol%. In the adhesive of Example 5, the viscosity is 567 Pa·s in a state before curing. In the adhesive of Example 5, the magnetic permeability is 2.0 in a state after curing. In the adhesive of Example 5, the glass transition temperature is 125° C. in a state after curing. In the adhesive of Example 5, the adhesive strength is 14 MPa in a state after curing.
[0057] In the adhesive of Example 6, the number average molecular weight of the bisphenol F type resin 51 is 340 g / mol. In the adhesive of Example 6, the volume ratio of the magnetic powder 52 is 30 vol%. In the adhesive of Example 6, the viscosity is 1143 Pa·s in the pre-cured state. In the adhesive of Example 5, the magnetic permeability is 2.2 in the cured state. In the adhesive of Example 6, the glass transition temperature is 125° C. in the cured state. In the adhesive of Example 6, the adhesive strength is 14 MPa in the cured state.
[0058] In the adhesive of Comparative Example 1, the number average molecular weight of the bisphenol F type resin 51 is 380 g / mol. In the adhesive of Comparative Example 1, the volume ratio of the magnetic powder 52 is 35 vol%. In the adhesive of Comparative Example 1, before curing, the viscosity is 3760 Pa·s. In the adhesive of Comparative Example 1, after curing, the magnetic permeability is 2.5. In the adhesive of Comparative Example 1, after curing, the glass transition temperature is 125° C. In the adhesive of Comparative Example 1, after curing, the adhesive strength is 14 MPa.
[0059] In the adhesive of Comparative Example 2, the number average molecular weight of the bisphenol F type resin 51 is 340 g / mol. In the adhesive of Comparative Example 2, the volume ratio of the magnetic powder 52 is 40 vol%. In the adhesive of Comparative Example 2, the viscosity is 4507 Pa·s in a state before curing. In the adhesive of Comparative Example 2, the magnetic permeability is 2.9 in a state after curing. In the adhesive of Comparative Example 2, the glass transition temperature is 125° C. in a state after curing. In the adhesive of Comparative Example 2, the adhesive strength is 14 MPa in a state after curing.
[0060] As a result of the comparison test of thread cutting time, the thread cutting time of the adhesive of Example 1 was 11 seconds. The thread cutting time of the adhesive of Example 2 was 12 seconds. The thread cutting time of the adhesive of Example 3 was 20 seconds. The thread cutting time of the adhesive of Example 4 was 10 seconds. The thread cutting time of the adhesive of Example 5 was 10 seconds. The thread cutting time of the adhesive of Example 6 was 11 seconds. The thread cutting time of the adhesive of Comparative Example 1 was 80 seconds. The thread cutting time of the adhesive of Comparative Example 2 was 80 seconds.
[0061] In the "Judgment" column of "Characteristics (before curing)" in Tables 1 and 2, ◯ indicates that the thread breakage time is 20 seconds or less, and × indicates that the thread breakage time is longer than 20 seconds. The above judgment value was determined as the boundary for whether or not there is a risk that the adhesive 50 dripping from the squeegee will adhere to something other than the printing target.
[0062] From the test results of Examples 1 to 6 and Comparative Example 1, it was found that the thread breakage time tended to be longer when the number average molecular weight of the bisphenol F resin 51 was large. That is, similar to the measurement results of the thread breakage time using the above-mentioned four types of samples, when the number average molecular weight of the bisphenol F resin 51 was greater than 360 g / mol, the rate of increase in the thread breakage time became rapidly large. In other words, it can be said that the number average molecular weight of the bisphenol F resin 51 is preferably 360 g / mol or less.
[0063] From the test results of Examples 1 to 6 and Comparative Example 2, it was found that the thread cutting time tended to be longer when the volume ratio of magnetic powder 52 was large. That is, similar to the measurement results of the thread cutting time using the above-mentioned five types of samples, when the volume ratio of magnetic powder 52 exceeded 35 vol%, the rate of increase in the thread cutting time became rapidly large. In other words, it can be said that the volume ratio of magnetic powder 52 is preferably 35 vol% or less.
[0064] Furthermore, in the case of the adhesive in Example 3 with a viscosity of 3223 Pa·s, the thread-breaking time was 20 seconds. On the other hand, in the case of the adhesive in Comparative Example 1 with a viscosity of 3760 Pa·s, the thread-breaking time was 80 seconds. From this, it is predicted that the inflection point of the change in thread-breaking time relative to the increase in viscosity is between 3223 Pa·s and 3760 Pa·s, that is, approximately 3500 Pa·s. Therefore, it can be said that the viscosity of the adhesive is preferably, for example, 3500 Pa·s or less.
[0065] The adhesives of Examples 1 to 6 all had a magnetic permeability exceeding 1.7 after curing. Thus, if the magnetic permeability exceeds 1.7, the adhesive is practically usable as the adhesive 50 for bonding the drum core 10C and the top plate 10F of the coil component 10. In other words, the adhesives of Examples 1 to 6 have a sufficient magnetic permeability value as the adhesive 50 for the coil component 10.
[0066] <Regarding Examples 2, 3, 7 to 9> The results of the comparative test of the adhesives of Examples 2, 3, and 7 to 9 will be described below.
[0067] [Table 2]
[0068] As shown in Table 2, the adhesive of Example 2 is the adhesive of Example 2 described above. That is, in this adhesive, the median particle size (D50) of the magnetic powder 52 is 0.8 μm. Moreover, the adhesive of Example 3 is the adhesive of Example 3 described above. That is, in this adhesive, the median particle size (D50) of the magnetic powder 52 is 0.8 μm.
[0069] In the adhesive of Example 7, the number average molecular weight of the bisphenol F type resin 51 is 340 g / mol. In the adhesive of Example 7, the volume ratio of the magnetic powder 52 is 35 vol%. In the adhesive of Example 7, the median particle size (D50) of the magnetic powder 52 is 0.5 μm. In the adhesive of Example 7, the viscosity before curing is 2911 Pa s.
[0070] In the adhesive of Example 8, the number average molecular weight of the bisphenol F type resin 51 is 360 g / mol. In the adhesive of Example 8, the volume ratio of the magnetic powder 52 is 35 vol%. In the adhesive of Example 8, the median particle size (D50) of the magnetic powder 52 is 1.5 μm. In the adhesive of Example 8, the viscosity before curing is 1820 Pa s.
[0071] In the adhesive of Example 9, the number average molecular weight of the bisphenol F type resin 51 is 340 g / mol. In the adhesive of Example 9, the volume ratio of the magnetic powder 52 is 25 vol%. In the adhesive of Example 9, the median particle size (D50) of the magnetic powder 52 is 2.5 μm. In the adhesive of Example 9, the viscosity before curing is 1137 Pa s.
[0072] As a result of the comparison test of thread breakage time, the thread breakage time of the adhesive of Example 7 was 16 seconds, the thread breakage time of the adhesive of Example 8 was 11 seconds, and the thread breakage time of the adhesive of Example 9 was 11 seconds.
[0073] From the test results of Examples 2, 3, and 7 to 9, when the median particle size (D50) of the magnetic powder 52 was within the range of 0.8 μm or more and 2.5 μm or less, the thread breakage time was 20 seconds or less. Furthermore, from the test results, the smaller the median particle size (D50) of the magnetic powder 52 in the adhesive 50, the greater the viscosity tends to be. From this, it can be said that it is preferable that the median particle size (D50) of the magnetic powder 52 is 0.8 μm or more.
[0074] <Effects of this embodiment> (1) According to the above embodiment, the adhesive 50 contains the magnetic powder 52, and thus has a better magnetic permeability than an adhesive not containing the magnetic powder 52. On the other hand, the adhesive 50 has a tendency that the viscosity of the adhesive 50 increases as the number average molecular weight of the bisphenol F type resin 51 increases. Here, the number average molecular weights of bisphenol F type epoxy resins that are generally available on the market are known to be about 3300 g / mol and about 5500 g / mol. On the other hand, the number average molecular weight of the bisphenol F type resin 51 in the above embodiment is 312 g / mol or more and 360 g / mol or less, which is significantly smaller than the number average molecular weight of general bisphenol F type resins. By deliberately adopting the bisphenol F type resin 51 in such a number average molecular weight range, the viscosity of the adhesive 50 can be prevented from increasing.
[0075] Similarly, the greater the volume ratio of the magnetic powder 52 in the adhesive 50, the higher the viscosity of the adhesive 50 tends to be. In the above embodiment, the volume ratio of the magnetic powder 52 in the adhesive 50 is 35 vol% or less. With such a volume ratio of the magnetic powder 52, it is possible to prevent the viscosity of the adhesive 50 from becoming high.
[0076] As described above, the above configurations ensure the desired magnetic permeability of the adhesive 50 for the coil component 10, while simplifying handling during manufacturing. In particular, the adhesive 50 of the above embodiment can reduce thread breakage time when applying the adhesive 50 before hardening to the top plate 10F of the coil component 10 using a screen printer. In other words, the adhesive 50 is also preferable from the viewpoint of continuous printability.
[0077] (2) According to the above embodiment, the volume ratio of the magnetic powder 52 in the adhesive 50 is 20 vol % or more. With such a volume ratio of the magnetic powder 52, the adhesive 50 applied to the coil component 10 can obtain a preferable magnetic permeability.
[0078] (3) According to the above embodiment, the adhesive 50 contains the silane coupling agent 55. This configuration can improve the adhesive strength of the adhesive 50. In particular, in the above embodiment, the adhesive 50 is interposed between the drum core 10C and the top plate 10F. The silane coupling agent 55 is useful for adhesion to such inorganic substances.
[0079] (4) According to the above embodiment, the adhesive 50 contains the dispersant 56. With this configuration, the dispersant 56 can suppress aggregation of the magnetic powder 52. Therefore, even if the volume ratio of the magnetic powder 52 is relatively large, for example, aggregation of the magnetic powder 52 can be suppressed.
[0080] (5) According to the above embodiment, the glass transition temperature of the adhesive 50 is 125° C. or higher. That is, according to this configuration, the heat resistance of the adhesive 50 is improved. Therefore, even if the coil component 10 is used in a high-temperature environment, for example, it is possible to suppress a decrease in the reliability of the coil component 10.
[0081] (6) In the above embodiment, the median particle size (D50) of the magnetic powder 52 is 0.8 μm or more. The smaller the median particle size (D50) of the magnetic powder 52 in the adhesive 50, the greater the viscosity tends to be. From the results of the above-mentioned comparative test, if the median particle size (D50) of the magnetic powder 52 is 0.8 μm or more, the thread breakage time of the adhesive 50 can be prevented from becoming long.
[0082] (7) In the above embodiment, the median particle size (D50) of the magnetic powder 52 is 2.5 μm or less. The larger the median particle size (D50) of the magnetic powder 52, the more likely it is that the magnetic powder 52 will collide with each other within the adhesive 50. In other words, depending on the shape of the area to which the adhesive 50 is applied, the magnetic powder 52 may not conform to the shape of the area to which the adhesive 50 is applied and may become biased within the adhesive 50. If the median particle size (D50) of the magnetic powder 52 is within the above range, these problems are unlikely to occur.
[0083] (8) In the above embodiment, the adhesive strength of the adhesive 50 to alumina per 25 square millimeters is 10 MPa or more. By using an adhesive 50 having such adhesive strength, a preferable adhesive strength can be obtained in the coil component 10.
[0084] (9) In the above embodiment, the coil component 10 has a closed magnetic circuit made up of the flange 20 and the top plate 10F. In this way, using the adhesive 50 of the above embodiment as the adhesive 50 for bonding the flange 20 and the top plate 10F that form the closed magnetic circuit is particularly suitable for improving the characteristics of the coil component 10 as a whole.
[0085] <Example of change> The above embodiment and the following modified examples can be implemented in combination with each other to the extent that no technical contradiction occurs.
[0086] <Examples of changes to coil parts> The shape of the winding core 11 is not limited to the example of the above embodiment. For example, the shape of the winding core 11 may be a cylinder or a polygonal prism other than a quadrangular prism.
[0087] The configuration of the drum core 10C is not limited to the example of the above embodiment. For example, the drum core 10C may not have the first recess 21A and the second recess 22A. In this case, for example, it is sufficient that the first electrode 31 and the second electrode 32 are separated from each other, and the third electrode 33 and the fourth electrode 34 are separated from each other.
[0088] The material and shape of the external electrode 30 are not limited to those in the above embodiment. For example, the material of the plating layer of the external electrode 30 may be an alloy of tin or nickel. The external electrode 30 may not have a plating layer. In that case, the portion where the conductive metal layer is exposed may be used as the external electrode 30.
[0089] The coil device 10 may include at least one wire. When the number of wires is one, one external electrode 30 may be provided on the first flange 21 and one external electrode 30 may be provided on the second flange 22.
[0090] The coil component 10 is not limited to a configuration including a drum core 10C and a top plate 10F. The coil component 10 may have a first core around which a wire is wound and a second core connected to the first core via an adhesive 50. The first core and the second core may be bonded together by the adhesive 50.
[0091] <Examples of changes to adhesives> The adhesive 50 is not limited to be applied to the coil component 10. The adhesive 50 is preferably applied to an electronic component having a core made of a magnetic material.
[0092] The type of the hardener 53 in the adhesive 50 is not limited to the example in the above embodiment. Any hardener compatible with the bisphenol F type resin 51 may be used. The volume ratio of the magnetic powder 52 in the adhesive 50 may be 35 vol% or less. In other words, the volume ratio of the magnetic powder 52 in the adhesive 50 may be less than 20 vol%. The volume ratio of the magnetic powder 52 may be set so as to obtain a preferable magnetic permeability in the coil component 10 to be used.
[0093] The number average molecular weight of the bisphenol F type resin 51 in the adhesive 50 may be in the range of 312 g / mol or more and 360 g / mol or less. The adhesive 50 does not necessarily need to contain the silane coupling agent 55, the dispersant 56, and the curing accelerator 54. In addition, the types of the silane coupling agent 55, the dispersant 56, and the curing accelerator 54 are not limited to those in the above embodiment.
[0094] The glass transition temperature of the adhesive 50 after curing may be less than 125° C. The glass transition temperature may be any suitable value depending on the intended use of the adhesive 50. The median particle size (D50) of the magnetic powder 52 in the adhesive 50 may be less than 0.8 μm or more than 2.5 μm. The median particle size (D50) of the magnetic powder 52 may be any value that provides a preferable state for handling the adhesive 50.
[0095] After curing, the adhesive strength of the adhesive 50 to alumina may be less than 10 MPa per 25 mm 2. The adhesive strength of the adhesive 50 is preferably in a range that allows the top plate 10F and the drum core 10C to be sufficiently bonded together.
[0096] <Additional Notes> The technical ideas that can be derived from the above-described embodiments and modifications will be described below. [1] An adhesive containing a bisphenol F type resin, a curing agent for the bisphenol F type resin, and a magnetic powder, wherein the volume ratio of the magnetic powder to the adhesive is 35 vol% or less, and the number average molecular weight of the bisphenol F type resin is 312 g / mol or more and 360 g / mol or less.
[0097] [2] The adhesive according to [1], wherein the volume ratio of the magnetic powder in the adhesive is 20 vol % or more. [3] The adhesive according to [1] or [2], further comprising a silane coupling agent.
[0098] [4] The adhesive according to any one of [1] to [3], further comprising a dispersant for dispersing the magnetic powder. [5] The adhesive according to any one of [1] to [4], wherein the magnetic powder has a median particle size (D50) of 0.8 μm or more.
[0099] [6] The adhesive according to any one of [1] to [5], wherein the magnetic powder has a median particle size (D50) of 2.5 μm or less. [7] The adhesive according to any one of [1] to [6], which has a glass transition temperature of 125°C or higher after curing.
[0100] [8] The adhesive according to any one of [1] to [7], wherein after curing, the adhesive has an adhesive strength to alumina of 10 MPa or more per 25 square millimeters. [Explanation of symbols]
[0101] 10...Coil parts 10C…Drum core 10F…Tabletop 11...Core 20…Flange 30…External electrode 41…First wire 42…Second wire 50…Glue 51...Bisphenol F resin 52...Magnetic powder 53... Hardener 54...Cure accelerator 55...Silane coupling agent 56...Dispersants
Claims
1. An adhesive comprising a bisphenol F resin, a curing agent for the bisphenol F resin, and a magnetic powder, A volume ratio of the magnetic powder to the adhesive is 35 vol% or less, The number average molecular weight of the bisphenol F resin is 312 g / mol or more and 360 g / mol or less. glue.
2. The volume ratio of the magnetic powder to the adhesive is 20 vol % or more. The adhesive of claim 1.
3. Further contains a silane coupling agent The adhesive of claim 1.
4. Further contains a dispersant for dispersing the magnetic powder. The adhesive of claim 1.
5. The median particle size (D50) of the magnetic powder is 0.8 μm or more. The adhesive of claim 1.
6. The median particle size (D50) of the magnetic powder is 2.5 μm or less. The adhesive of claim 1.
7. After curing, the glass transition temperature is 125°C or higher. The adhesive of claim 1.
8. After curing, the adhesive has a bond strength of 10 MPa or more per 25 square millimeters to alumina. The adhesive of claim 1.
Citation Information
Patent Citations
Ferromagnetic adhesive
JP1989284573A
Magnetic bonding agent
JP1994215927A
Film adhesive and anisotropically conductive adhesive
JP2010150362A
Adhesive film for solar cell electrode and manufacturing method of solar cell module using the same
JP2012069913A
Coil component
JP2022061295A